Prevalence of obesity in Malay population in Malaysia based on the BMI status; A study in Terengganu - Hassan Basri, Mukhali; Ahmad Zubaidi, A.latif; Nordin, Simbak; Atif, Amin Baig; Norizan, Abdul Ghani (2017)
A normal health status is highly depends on body weight. Many health problems may occur or imposed risk for extremely obese individuals. BMI status may be useful to overcome the associated comorbidities. This study determined the prevalence of obesity and its types among adults, aged 19 – 60 years, in the Terengganu during 2015. A cross sectional study was conducted for a period of six months. A total of 340 subjects were recruited through volunteer sampling. The BMI was determined by the standard method. Well-appropriate antropometric calculations (BMI, waist circumference, hip circumference, fat percentage) were computed to assess the indices of obesity and its types. WHO classification for determining an obese subject was followed. BMI was determined for all the subjects and it was found that out of 340 subjects, a total of 95 subjects (27.9%) were found to be obese as per WHO criterion for BMI, a total of 122 subjects were overweight (35.8%) and normal BMI individuals were 123 (36.1%). To the best of our knowledge, this is the first report with a high subject size, reporting the prevalence of obesity in Malaysia (Terengganu) to be 27.6% with a prevalence of overweight to be 35.8%. There is a serious need to address this alarming prevalence of obesity by studying the genetics, nongenetics associated factors and diet related CVD risks for obese and overweight subjects in Terengganu and Malaysia.